2020
DOI: 10.1002/jhbp.878
|View full text |Cite
|
Sign up to set email alerts
|

Natural history and optimal treatment strategy of intraductal papillary mucinous neoplasm of the pancreas: Analysis using a nomogram and Markov decision model

Abstract: Background/Purpose: With the increase in detection of intraductal papillary mucinous neoplasms (IPMN), a tailored approach is needed. This study was aimed at exploring the natural history of IPMN and suggest optimal treatment based on malignancy risk using a nomogram and Markov decision model. Methods: Patients with IPMN who underwent surveillance or surgery were included. Changes in worrisome features/high-risk stigmata and malignancy conversion rate were assessed. Life expectancy and quality-adjusted life ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“… 15 In a similar analysis of over 1700 presumed BD-IPMNs, Han et al found a 19% and 35% cumulative risk of developing a worrisome feature or high-risk stigmata at 5- and 10-year follow-up, respectively. 16 These results highlight the fact that having a BD-IPMN in general confers a higher risk of developing a pancreatic cancer even after long-term surveillance. It may be that surveillance discontinuation should be tailored to the age of the patient.…”
Section: Long-term Surveillance Of Presumed Branch Duct (Bd)-ipmnmentioning
confidence: 67%
“… 15 In a similar analysis of over 1700 presumed BD-IPMNs, Han et al found a 19% and 35% cumulative risk of developing a worrisome feature or high-risk stigmata at 5- and 10-year follow-up, respectively. 16 These results highlight the fact that having a BD-IPMN in general confers a higher risk of developing a pancreatic cancer even after long-term surveillance. It may be that surveillance discontinuation should be tailored to the age of the patient.…”
Section: Long-term Surveillance Of Presumed Branch Duct (Bd)-ipmnmentioning
confidence: 67%
“…Intraductal papillary‐mucinous neoplasm (IPMN) invades other organs, leading to the formation of fistulas 1‐4 . IPMN can potentially become malignant 5 . We report a case of intraductal papillary‐mucinous carcinoma (IPMC) that formed a fistula between the stomach and colon, which was confirmed preoperatively.…”
Section: Introductionmentioning
confidence: 80%
“…[1][2][3][4] IPMN can potentially become malignant. 5 We report a case of intraductal papillary-mucinous carcinoma (IPMC) that formed a fistula between the stomach and colon, which was confirmed preoperatively.…”
Section: Introductionmentioning
confidence: 87%
“…Several studies suggested nomograms predicting individual risk of malignancy or malignant progression to provide tailored treatment for BD-IPMN. 29,30 Individualized risk stratification for MD-involved IPMN has been challenging. We anticipate that a customized approach could be performed by applying currently available nomograms using MPD diameter as a predictor or establishing a nomogram fit for the MD involving type.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested nomograms predicting individual risk of malignancy or malignant progression to provide tailored treatment for BD‐IPMN 29,30 . Individualized risk stratification for MD‐involved IPMN has been challenging.…”
Section: Discussionmentioning
confidence: 99%